Magnetic Nanoparticles Detection of C-Reactive Protein Combined with Neutrophil to Lymphocyte Ratio to Predict the Occurrence of Anastomotic Fistula after Rectal Cancer Surgery: Magnetic nanoparticles Detection of CRP - Song, Guolei; Guo, Han; Jiang, Congqiao; Shi, Yi; Liu, Mulin (Cellular and Molecular Biology, 2022)
It aimed to explore the effect of C-reactive protein (CRP) combined with neutrophil to lymphocyte ratio (NLR) in the early prediction of anastomotic leakage (AL) after rectal cancer surgery and to improve the prediction accuracy. In this study, gold (Au)/ferroferric oxide (Fe3O4) magnetic nanoparticles were first synthesized and modified with polyacrylic acid (PAA). After modification, they underwent CRP antibody detection. Then, 120 patients with rectal cancer who underwent Dixon surgery were selected as the research objects to investigate the sensitivity and specificity of CRP combined with NLR in predicting AL. It was found that the diameter of the Au/Fe3O4 nanoparticles prepared in this study was about 45 nm. After adding 60 μg of antibody, the diameter of PAA-Au/Fe3O4 was 226.5 nm, the dispersion coefficient was 0.16, the standard curve between CRP concentration and luminous intensity was y = 8,966.5 x + 2,381.3, and R2 = 0.9944. Besides, the correlation coefficient was R2 = 0.991, and the linear regression equation was y=1.103 x - 0.0022 compared with the nephelometric method. By analyzing the receiver operating characteristic (ROC) curve of CRP combined with NLR to predict AL after Dixon surgery, the cut-off point was 0.11 on the first day after the surgery, the area under the curve was 0.896, the sensitivity was 82.5%, and the specificity was 76.67%. The cut-off point on the third day after the surgery was 0.13, the area under the curve was 0.931, the sensitivity was 86.67%, and the specificity was 90%. On the fifth day after the surgery, the cut-off point, the area under the curve, the sensitivity, and the specificity were 0.16, 0.964, 92.5%, and 95.83% in turn. In conclusion, PAA-Au/Fe3O4 magnetic nanoparticles could be used for clinical examination of patients with rectal cancer, and CRP combined with NLR could improve the prediction accuracy of AL after rectal cancer surgery.